Determinants of Internet Addiction in Private University Students - Akmal Akmal (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
Digital transformation has increased the intensity of internet use among students, which on one hand supports academic activities, but on the other hand has the potential to lead to internet addiction. This study aims to analyse the influence of resilience on loneliness and life satisfaction, as well as the influence of resilience, loneliness, and life satisfaction on internet addiction in private university students. This research uses a quantitative approach with a survey method applied to 280 undergraduate students from the 2021 intake at Bung Hatta University. Data were collected using a structured questionnaire and analysed with Partial Least Squares–Structural Equation Modelling (PLS-SEM) using SmartPLS 4.0. The research results indicate that resilience significantly influences loneliness and life satisfaction. Loneliness and life satisfaction also significantly influence internet addiction, with loneliness being the most dominant factor. Additionally, resilience has been proven to significantly influence internet addiction. This finding indicates that internet addiction in college students is influenced by the interconnected dynamics of psychological factors. Therefore, efforts to prevent internet addiction in college settings need to focus on strengthening psychological resilience, increasing life satisfaction, and reducing loneliness through adequate social support.